Gender-based violence, a hidden reality within the pandemic (2022)
This document analyzes the situation of women in the framework of compulsory isolation due to COVID-19. It is recognized that the sexual distinction of work, sustained in a patriarchal social structure, affects and deteriorates in all aspects, the quality of life of women. Of particular note are the reports from governmental and non-governmental institutions that indicate a significant increase in gender-based violence during the pandemic. Among the many flaws and shortcomings that the confinement situation due to Covid-19 has exposed, are the inequalities and exhausting working and therefore economic conditions of women, which end up affecting their autonomy and putting their lives at risk. Thus, it is identified that the pandemic has turned out to be for women in a new oppressive context, so daily life has become more difficult to remain permanently at risk their physical and mental integrity. Finally, it is proposed that a work from the feminist perspective will make possible scenarios of recognition and equity for women.